Parallel high-throughput screening of polymer vectors for nonviral gene delivery: Evaluation of structure-property relationships of transfection - Rinkenauer, Alexandra C.; Vollrath, Antje; Schallon, Anja; Tauhardt, Lutz; Kempe, Kristian; Schubert, Stephanie; Fischer, Dagmar; Schubert, Ulrich S. (ACS Combinatorial Science, 2013)
In recent years, "high-throughput" (HT) has turned into a keyword in polymer research. In this study, we present a novel HT workflow for the investigation of cationic polymers for gene delivery applications. For this purpose, various poly(ethylene imine)s (PEI) were used as representative vectors and investigated via HT-assays in a 96-well plate format, starting from polyplex preparation up to the examination of the transfection process. In detail, automated polyplex preparation, complex size determination, DNA binding affinity, polyplex stability, cytotoxicity, and transfection efficiency were performed in the well plate format. With standard techniques, investigation of the biological properties of polymers is quite time-consuming, so only a limited number of materials and conditions (such as pH, buffer composition, and concentration) can be examined. The approach described here allows many different polymers and parameters to be tested for transfection properties and cytotoxicity, giving faster insights into structure-activity relationships for biological activity. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2020-10-13
Keywords: combinatorial workflow; heparin; high-throughput screening; nonviral gene delivery; poly(ethylene imine); polyplex stability; transfection